Ihdad bagi Perempuan Pekerja Perspektif Maslahah (Studi di Kecamatan Lubuk Pinang Kabupaten Mukomuko) - Harobin, Zainal; Rohimin, Rohimin; Nurdin, Zurifah (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2025)
Abtstract : The aims of this research are: First, to find out whether working women in Lubuk Pinang District, Mukomuko Regency position the period of ihdad from a maslahah perspective. Second, to find out the obstacles to ihdad for working women in Lubuk Pinang District, Mukomuko Regency from a maslahah perspective. This type of research is descriptive qualitative research. This research concludes that: First, the realization of ihdad for women who work after the death of their husbands in Lubuk Pinang District, Lubuk Pinang is not yet perfect due to job demands. Ihdad, a working woman whose husband died in Lubuk Pinang District, is more focused on maintaining family life because of the necessities of life that must be met. There are three categories of ihdad realization, namely: not knowing ihdad and not implementing ihdad, knowing but not implementing ihdad and knowing and implementing ihdad.  Second, the obstacles to ihdad for working women whose husbands have died in Lubuk Pinang District consist of the economy and job demands, their husband's knowledge and work during life are included in maslahah al-dharuriyat which is directly related to basic human needs both in this world and the hereafter.Keywords: ihdad, women, maslahah. Abstrak : Tujuan penelitian ini adalah : Pertama, untuk mengetahui perempuan pekerja di Kecamatan Lubuk Pinang Kabupaten Mukomuko memposisikan masa ihdad perspektif maslahah. Kedua, untuk mengetahui hambatan ihdad bagi perempuan pekerja di Kecamatan Lubuk Pinang Kabupaten Mukomuko perspektif maslahah.. Jenis penelitian ini adalah penelitian deskriptif kualitatif. Penelitian ini menyimpulkan bahwa: Pertama, Realisasi ihdad perempuan yang bekerja setelah kematian suami di Kecamatan Lubuk Pinang Lubuk Pinang belum sempurna dikarenakan adanya tuntutan pekerjaan. Ihdad perempuan pekerja yang ditinggal mati suami di Kecamatan Lubuk Pinang lebih fokus pada menjaga kehidupan keluarga karena kebutuhan hidup yang harus dipenuhi. Ada tiga katagori realisasi ihdad yaitu: tidak mengetahui ihdad dan tidak menjalankan ihdad, mengetahui tapi tidak menjalankan ihdad dan mengetahui dan menjalankan ihdad.  Kedua, Hambatan ihdad bagi perempuan pekerja yang ditinggal mati suaminya di Kecamatan Lubuk Pinang terdiri dari Ekonomi dan tuntutan pekerjaan, pengetahuan dan pekerjaan suami semasa hidup termasuk ke dalam maslahah al-dharuriyat yang berhubungan langsung dengan kebutuhan dasar manusia baik di dunia maupun akhirat.Kata Kunci : ihdad, perempuan, maslahah.